Assistance In the Preparation of SWOT Analysis On MSMEs Sambikrep District Surabaya City - Sitepu*, Sri Nathasya Br; Efrata, Tommy Christian (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
MSMEs in Sambikerep District were affected by the Covid-19 pandemic which was marked by a decline in business performance. MSMEs need strategies based on business analysis to improve the performance of business units. SWOT analysis (Strength, Weakness, Opportunity, Threat) is an internal and external analysis to determine business unit strategies. Community service activities in the form of assistance in the preparation of SWOT analysis were given to MSME actors in Sambicrep District, Surabaya City. Assistance was provided to 20 MSME actors (MSME owners). This mentoring activity was carried out in October in four meetings. The training method is provided offline which consists of several activities, namely: internal analysis, external analysis, mentoring, preparation and presentation of SWOT matrix and determination of business strategy. The purpose of mentoring activities is to provide knowledge on the preparation of business analysis (SWOT analysis) so that MSME actors can compile business strategies to improve business unit performance. The results of mentoring activities: 1) MSME actors compile Internal Factor Analysis Summary (IFAS) analysis, 2) Factors Analysis Summary (EFAS), 3) SWOT matrix, 4) strategies to develop MSMEs